Development of Biotechnologies and Bioterrorism - A. S. Kontsevenko (Московский журнал международного права, 2009)
All the states meet real or potential menace of terrorism. Legislation of the European countries attributes international terrorism to the most dangerous criminal offence. International law marks out “technological terrorism” as a very dangerous variety of international terrorism. It concerns the usage of the nuclear weapons, radiological weapons, chemical weapons or biological weapons or its components, pathogens and other radioactive materials that cause harm for people. Biotechnologies can reduce to the terrible consequences if the mankind does not control its’ development. Compactness of the material, easiness of the delivery, really hard possibility to be found – all that makes biological means of terror rather perspective for terrorists. In order to minimize the risk of bioterrorism governments should collaborate in the field of prevention, warning and exchange of information.